Handbook of the history of social psychology - Kruglanski, Arie W.; Stroebe, Wolfgang (New York : Psychology Press, 2012)
'This is the first ever handbook to comprehensively cover the historical development of the field of social psychology, including the main overarching approaches and all the major individual topics. Contributors are all world-renowned scientists in their subfields who engagingly describe the people, dynamics, and events that have shaped the discipline'--
Includes bibliographical references.
Keywords: Social psychology -- History -- Handbooks, manuals, etc; Social psychology